Philosophical anhistological assessment of diclofenac sodium on the heart of local rabbits (Journal of Pharmaceutical Negative Results, 2022)
The current Study was done to show the physiological and histological defect at different doses of diclofenac sodium on heart of Rabbits twenty rabbits was divided into four groups the therapeutic group (T) , over does group1(T1), over dose group2 (T2) and control group each group was injected intraperitoniali by ( T,T1 ,T2 ) mg/kg and Distiled water, respectively for 14 days, at the fourteen day of experimental animals were sacrificed, blood sample collected and heart was fixed immediately in 10% formalin for histological preparation and obtained serum for physiological test the result was revealed , T group significant decreases in lipoproteins so as to significant of low density-lipoproteins on ( p < 0.05 ) ( VLDL-C ). on the other hands the results showed significant differences on level of creatine kinase , troponin and lactate dehydrogenase , and in T2 group significant decreases of creatine kinase ,troponin and lactate dehydrogenase on ( P < 0.05 ) compared with control group. The histological examination of T groups was revealed degeneration in muscles fibers, zonal vacuolation around the nucleus of muscle fiber the result of T2 groups showed, atrophy in muscle fibers degeneration was appear of whole section spread out at inflammatory cells in between muscle fibers and zonal vacuolation around nucleus of muscle fibers. The results obtained from T2 groups was show atherosclerosis on marginal blood vessels of heart, hemolysis of RBCs with spread out of hemocidrin out of blood vessels.